Molecular characterisation of the plasmodium falciparum pfcrt gene involved in chloroquine resistance - Lau, Hui Chong (Universiti Malaysia Sarawak (UNIMAS), 2008)
Chloroquine (CQ) resistant P. falciparum was first reported in the 1960s at the Thai-Cambodia border. Gradually CQ resistance has spread and is found in all regions where P. falciparum transmission occurs. The emergence of CQ resistance due to excessive CQ selection pressure on the parasite populations has become an important issue because of the higher mortality and morbidity associated with drug resistance. Currently CQ is no longer recommended to treat falciparum malaria. CQ resistance in P. falciparum has been attributed to a single amino acid substitution on the P. falciparum chloroquine resistant transporter (pfcrt) at position 76 where Iysine is substituted with threonine (K76T). Molecular studies showed that CQ resistance emerged independently at five different geographical locations namely: Southeast Asia, two sites in South America, Papua New Guinea and the Philippines. Further analysis of resistant isolates revealed 22 additional non-silent amino acid substitutions on the pfcrt gene with a new amino acid substitution detected in the study reported here.